Hilary Putnam, the evolution of realism and the pragmatist point of view - Mayoral, Juan Vicente (Analysis. Journal of Philosophical Research, 2018)
This essay is an introduction to the issue of the journal Análisis devoted to thephilosophy of Hilary Putnam. This paper provides a thematic introduction to Putnam’sthought, though some indications concerning his intellectual development are alsoincluded. It begins with Putnam’s work on realism, whether metaphysical, internalor natural; then it deals with Putnam’s relations with classic authors of Americanpragmatism as William James and John Dewey. In the last section, before concludingremarks, Putnam’s position concerning the interpretation of quantum mechanics isbriefly shown. Each section includes an exposition of the essays that make up thisissue as well as their relations with the themes previously expounded.